2021
DOI: 10.1270/jsbbs.20129
|View full text |Cite
|
Sign up to set email alerts
|

The <i>temperature sensitive hybrid breakdown 1</i> induces low temperature-dependent intrasubspecific hybrid breakdown in rice

Abstract: Hybrid breakdown (HB) is an important type of post-zygotic reproductive barrier that inhibits hybrid production during the process of cross-breeding. A novel low temperature-dependent HB was identified in a chromosomal segment substitution line (CSSL) library derived from a cross of two rice ( Oryza sativa L. japonica ) cultivars, Yukihikari and Kirara397. A set of weakness symptoms in a target CSSL was observed at 23°C, but was rescued at 27°C and/or 30°C. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition, hybrid weakness is triggered by low temperature after germination. In rice, the temperature sensitivity was reported by the previous studies such as Hwc genes ( Saito et al, 2007 ), hw3/hw4 genes ( Fu et al, 2013 ), thb1 ( Yoneya et al, 2021 ) where low temperature enhanced the weakness, while Hwi genes ( Chen et al, 2013 ) enhanced the weakness at high temperature.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, hybrid weakness is triggered by low temperature after germination. In rice, the temperature sensitivity was reported by the previous studies such as Hwc genes ( Saito et al, 2007 ), hw3/hw4 genes ( Fu et al, 2013 ), thb1 ( Yoneya et al, 2021 ) where low temperature enhanced the weakness, while Hwi genes ( Chen et al, 2013 ) enhanced the weakness at high temperature.…”
Section: Discussionmentioning
confidence: 67%
“…In general, several hybrid weakness cases in some plants were reported to be low temperature-dependent and phenotypes of weak plants were rescued at high temperature ( Saito et al, 2007 ; Alcázar et al, 2009 ; Shiragaki et al, 2021 ; Yoneya et al, 2021 ). To date, only one high temperature-dependent hybrid weakness in rice was reported ( Chen et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of marker segregation distortion in this BC5F2 population might be due to that the population is already an advanced backcross population with high level genetic background of Ciherang as the recipient parent or the genetic distance between Ciherang and Rathu Heenati is likely close. A previous study also reported no segregation distortion found in the BC4F2 rice population produced by an intraspecific cross between YK3CSSL-6.1 and Kirara397 [29]. Segregation distortion is commonly found in crosses among divergent genotypes [30].…”
Section: Genotype and Segregation Analysesmentioning
confidence: 81%
“…R or R-like proteins of NB-LRR type play a receptor-like function and participate in specific recognition of pathogens, which are likely the causal temperature-sensitive component in defense responses [ 41 ]. High temperature usually decreases plant resistance, but it occasionally activates resistance [ 15 , 41 , 47 , 48 , 49 , 50 , 51 ]. In this study, the scr8 showed dwarf, short root phenotype, and the resistance to Xoo was enhanced more than wildtype under high temperature in filed.…”
Section: Discussionmentioning
confidence: 99%